2016
DOI: 10.1016/j.anbehav.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Inequity aversion strategies between marmosets are influenced by partner familiarity and sex but not by oxytocin

Abstract: Cooperation among individuals depends, in large part, on a sense of fairness. Many cooperating non-human primates (NHPs) show inequity aversion, (i.e., negative responses to unequal outcomes), and these responses toward inequity likely evolved as a means to preserve the advantages of cooperative relationships. However, marmosets (Callithrix spp.) tend to show little or no inequity aversion, despite the high occurrence of prosociality and cooperative-breeding in callitrichid monkeys. Oxytocin [OXT] has been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 93 publications
1
26
0
Order By: Relevance
“…The social-context manipulations for both the long-separation (7 hr) and the short-separation (15 min) challenges were preceded by a 30-minsocial isolation for drug uptake(Figure 1). The data for these experiments were collected during earlier studies (Cavanaugh et al, 2016; Mustoe et al, 2015; Mustoe, Harnisch, Hochfelder, Cavanaugh, & French, 2016) and have not been previously published.…”
Section: | General Methodsmentioning
confidence: 99%
“…The social-context manipulations for both the long-separation (7 hr) and the short-separation (15 min) challenges were preceded by a 30-minsocial isolation for drug uptake(Figure 1). The data for these experiments were collected during earlier studies (Cavanaugh et al, 2016; Mustoe et al, 2015; Mustoe, Harnisch, Hochfelder, Cavanaugh, & French, 2016) and have not been previously published.…”
Section: | General Methodsmentioning
confidence: 99%
“…2010); though OTA doesn’t always have this effect (Cavanaugh et al . 2014; Mustoe et al 2015; Mustoe et al . 2016).…”
Section: Mate-directed Behaviormentioning
confidence: 99%
“…(2014) found that Pro 8 -OT enhanced the amount of time spent in close proximity with their mate during a partner-preference test but in females only, while Leu 8 -OT had no effect for both males and females. However, the vast majority of findings in marmosets suggest that both OT ligands produce little to no effects on mate-directed behaviors including social approach, grooming, or huddling behaviors (all affiliative behaviors associated with pair-bond maintenance) (Cavanaugh et al 2014; Cavanaugh et al 2015); cooperative food sharing in a experimental prosocial food-sharing tasks (Mustoe et al 2015; Mustoe et al 2016); and affiliative behaviors (time in proximity, grooming, huddling) upon reunion following a long-term social separation (Cavanaugh et al unpubl data). While it would seem most likely that Pro 8 -OT treatments would produce larger effects on mate-directed behavior than Leu 8 -OT in marmosets, the data suggest there are minimal OT-specific effects.…”
Section: Mate-directed Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The studies examining the effects of neuropeptides on social behavior in NWM are increasingly important because they repeatedly demonstrate that neuropeptides do not universally enhancing sociality and, in some cases, neuropeptides like OT have no significant influence on socially-relevant behavior (Mustoe et al, 2016). Rather these studies support the more nuanced view that neuropeptides alter sociality in ways that reflect species-specific social relationships and social contexts.…”
Section: Neuropeptide Diversity and Social Behavior In New World Mmentioning
confidence: 99%